2020
DOI: 10.1038/s41467-020-16100-3
|View full text |Cite
|
Sign up to set email alerts
|

Budding yeast complete DNA synthesis after chromosome segregation begins

Abstract: To faithfully transmit genetic information, cells must replicate their entire genome before division. This is thought to be ensured by the temporal separation of replication and chromosome segregation. Here we show that in 20-40% of unperturbed yeast cells, DNA synthesis continues during anaphase, late in mitosis. High cyclin-Cdk activity inhibits DNA synthesis in metaphase, and the decrease in cyclin-Cdk activity during mitotic exit allows DNA synthesis to finish at subtelomeric and some difficult-to-replicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Mitotic DNA repair synthesis (MiDAS) has been documented as a means to complete replication of hard-to-duplicate genome features such as common fragile sites and telomeres ( Özer and Hickson, 2018 ). Moreover, in the unperturbed cell cycles of both yeast ( Ivanova et al, 2020 ; Torres-Rosell et al, 2007 ) and mammalian cells ( Moreno et al, 2016 ) onset of mitosis has been documented in the presence of under-replicated genomic regions, leading to DNA synthesis in offspring cells. These findings suggest that a temporal separation between DNA replication and chromosome segregation does not seem to be a strict rule for eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotic DNA repair synthesis (MiDAS) has been documented as a means to complete replication of hard-to-duplicate genome features such as common fragile sites and telomeres ( Özer and Hickson, 2018 ). Moreover, in the unperturbed cell cycles of both yeast ( Ivanova et al, 2020 ; Torres-Rosell et al, 2007 ) and mammalian cells ( Moreno et al, 2016 ) onset of mitosis has been documented in the presence of under-replicated genomic regions, leading to DNA synthesis in offspring cells. These findings suggest that a temporal separation between DNA replication and chromosome segregation does not seem to be a strict rule for eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite segregation of under-replicated chromosomal regions being mutagenic ( Durkin and Glover, 2007 ; Debatisse et al, 2012 ; Song et al, 2014 ), increased cell division rate in these circumstances may compensate for loss of fitness due to mutations. Also, if segregation of under-replicated loci is limited to specific genome compartments, such as the telomeres and subtelomeres, these may serve as a genetic playground, with higher mutation and copy-number variation allowing for increased genetic diversity, as has been proposed in yeast ( Ivanova et al, 2020 ; Brown et al, 2010 ). Consistent with this idea, our data suggest that chromosome subtelomeric DNA replication is mainly detectable at the temporal extremes of the conventional Leishmania S phase (either very early in S phase, as seen with the G1 enriched population; or very late in S phase, as seen with the G2/M enriched populations), and such regions have been demonstrated to be particularly prone to copy- number variation ( Bussotti et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different properties of Cdc28 variants found in our study advocates for the existence of several ways of suppression of pol2rc-ΔN defect. One explanation is based on the observation that the proper level of Cdc28 is required to complete the cell cycle when replication extends beyond chromosome segregation [79]. In the pol2rc-ΔN cells, the proportion of under-replicated genomic regions might be higher than in normal cells, as indicated by aberrant cell and nucleus morphology (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These regions would include centromeres, G-quadruplex, fragile sites, transposable elements, non-coding RNAs and subtelomeric regions [18,54,[59][60][61]. Very recently, another paper has shown that pericentromeric regions accumulate DNA damage markers during S-phase [62].…”
Section: Discussionmentioning
confidence: 99%